STUDENTS’ RESPONSES AND BEHAVIOURS TOWARD THE USE OF EDUCATIONAL DIGITAL STORYTELLING - Baehaki, Fatur (Journal of English Teaching and Linguistics Studies (JET Li), 2023)
Digital storytelling is widely applied on schools. However, in educational terms, digital storytelling has brought students to give various responses and behaviours from the use of educational digital storytelling on specific English subject. These responses and behaviours affect the eminence of educational digital storytelling whether as good learning tool for English subject or not.  The research intended to investigate what students’ responses and behaviours toward the use of educational digital storytelling (EDS) are. The research was conducted on SMAN 1 Dramaga and 21 respondents were chosen in this research. The researcher used qualitative approach and descriptive analysis. To get the research data, the researcher used triangulation techniques that consist of observation, questionnaire and interview.  The study reveals that there are occurring responses consisting visual and auditory responses after they watched EDS as well as the response styles. The students’ behaviours showed by the indication of classical conditioning and operant conditioning.